The MORAL ADVENTURE: EDUKASI KARAKTER SANTUN MELALUI BOARDGAME INTERAKTIF DI KALANGAN ANAK SD - Wahyudi, Agus Wahyudi,; Rulyansah, Afib; Rahayu, Dewi Widiana; Syaiful, Yuanita (Jurnal Likhitaprajna, 2025)
Strengthening moral values in elementary school-aged children is a crucial aspect in fostering social responsibility from an early age. However, amidst the digital age and the decline of face-to-face interaction, the practice of saying "sorry," "please," and "thank you" is beginning to be marginalized. This community service activity aims to instill basic values of good manners as a foundation for social responsibility through the educational board game Moral Adventure. This activity was carried out with fourth-grade students of SDN Tenggilis Mejoyo 1 Surabaya using a participatory-educational approach. Through a series of activities such as socialization, game guidance, and reflection sessions, children were encouraged to understand and practice moral values in situations that resemble real life. The implementation results showed an increase in students' understanding of the importance of mutual respect, empathy, and collaboration among peers. In addition to being a fun learning tool, the Moral Adventure board game also strengthens the school's role as a partner in instilling civic values and building a culture of good manners in elementary education environments.